2016
DOI: 10.1175/jcli-d-15-0222.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal–Interannual Variation and Prediction of Wet and Dry Season Rainfall over the Maritime Continent: Roles of ENSO and Monsoon Circulation

Abstract: The authors analyze the seasonal–interannual variations of rainfall over the Maritime Continent (MC) and their relationships with El Niño–Southern Oscillation (ENSO) and large-scale monsoon circulation. They also investigate the predictability of MC rainfall using the hindcast of the U.S. National Centers for Environmental Prediction (NCEP) Climate Forecast System version 2 (CFSv2). The seasonal evolution of MC rainfall is characterized by a wet season from December to March and a dry season fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 56 publications
4
45
0
3
Order By: Relevance
“…Their relationships with other ocean-atmosphere anomalies are generally well predicted in the model, except some overestimations which may be attributed to the overestimated impact of ENSO (figures not shown; Liang et al 2009;Zhang et al 2016a). The high prediction skills of these modes as well as their related features come from the high skill of ENSO predicted by the CFSv2, consistent with previous studies (Xue et al 2013;Zhang et al 2016a, b).…”
Section: The Most Predictable Enso Patternmentioning
confidence: 61%
See 1 more Smart Citation
“…Their relationships with other ocean-atmosphere anomalies are generally well predicted in the model, except some overestimations which may be attributed to the overestimated impact of ENSO (figures not shown; Liang et al 2009;Zhang et al 2016a). The high prediction skills of these modes as well as their related features come from the high skill of ENSO predicted by the CFSv2, consistent with previous studies (Xue et al 2013;Zhang et al 2016a, b).…”
Section: The Most Predictable Enso Patternmentioning
confidence: 61%
“…Beginning on 1 January of every year, the 9-month hindcasts have initial conditions at 0000 UTC, 0600 UTC, 1200 UTC, and 1800 UTC on every 5th day, forming a monthly 24-member ensemble. Details about the 9-month hindcast runs can be seen in Zhang et al (2016a), and further information about the initial time can be found at http://cfs.ncep.noaa.gov/cfsv2.info/. For convenience, the hindcast ensemble means at 0-month lead, 1-month lead, and so on to a 9-month lead are denoted as LM0, LM1, through LM9, respectively.…”
Section: Modelmentioning
confidence: 99%
“…Higher precipitation during winter is associated with the Asian monsoon (December-February), which is characterized by eastward winds from the Indian Ocean and southward winds from Asia (Yasunari 1981). Both the amount and the spatial distribution of winter precipitation show high interannual variation that is generated by the anomaly of the tropical Pacific Ocean air-sea heat exchange related to the El Niño-Southern Oscillation (ENSO) (Bjerknes 1969;Cane and Zebiak 1985;Hendon 2003;Yanto et al 2016;Lestari et al 2016;Hidayat et al 2016;Zhang et al 2016). For instance, warmer sea-surface temperatures (SSTs) over the eastern Pacific Ocean during El Niño events encourage convective activity to shift eastward.…”
Section: Introductionmentioning
confidence: 99%
“…The MC is located in the core of the strongest monsoon region of the world, and lies within the area of the warmest ocean which leads to large amounts of moist convection and heat release that favor rising motion over the region [7][8][9][10][11][12][13][14][15][16]. Thus, the MC plays an important role in variations of global climate [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. For example, latent heat release from rainfall or convective activity over the MC modulates the rainfall over East Asia through the Hadley cell, and favors tropical cyclone formation [2,23,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed a robust dry bias over the MC for wet and dry seasons and indicated that the dry bias exists in most dynamical models [40][41][42][43][44][45]. Spatially incoherent rainfall over the MC in the wet season leads to an "incoherent unpredictable" feature, especially for the western MC rainfall which tends to be uncorrelated with the sea surface temperature (SST) in the wet season [29,31]. Moreover, several studies have reported that a deficient representation of rainfall (or convection) exists in dynamical models [46][47][48].…”
Section: Introductionmentioning
confidence: 99%